Precious Data from Tiny Samples: Revealing the Correlation Between Energy Content and the Chemical Oxygen Demand of Municipal Wastewater by Micro-Bomb Combustion Calorimetry - Korth, Benjamin; Heber, Claudia; Normant-Saremba, Monika; Maskow, Thomas; Harnisch, Falk (Frontiers in Energy Research, 2021)
Wastewater treatment plants are aimed to be transformed from sinks into sources of energy and material. For fostering corresponding engineering efforts and economic assessments, comprehensive knowledge of the energy content of wastewater is required. We show that this data can be gathered by combining micro-bomb combustion calorimetry with freeze-drying. Thereby, the methodology for measuring the combustion enthalpy (∆cH) of wastewater is improved significantly by decreasing the time demand for the drying process as only tiny amounts of samples are required. Here, the primary clarifier of a wastewater treatment plant mainly treating municipal wastewater was weekly sampled during one year yielding 53 composite samples that were analyzed for ∆cH and standard wastewater parameters. A robust correlation between chemical oxygen demand and ∆cH of −14.9±3.5 kJ gCOD−1 (r=0.51) was determined verifying previous results obtained with more laborious and time-demanding methodologies. A stronger correlation was observed between ∆_c H and the biochemical oxygen demand (BOD5, r=0.64) suggesting its usage for predicting the potential of wastewater as feedstock for biotechnological applications. This demonstrates that micro-bomb combustion calorimetry can be applied for deriving precious information on the energy content of wastewater from simple COD measurements.